Digital Promotional Content Training to Increase Tourist Attraction - Fajar Adhi Kurniawan; Muh. Luthfi Hakim; M Sofyan Alnashr (LP2M of Institute for Research and Community Services - UIN Walisongo, 2022)
Digital content is a promotional medium that is growing and in demand at present, including promoting tourist destinations. Ease of access and a broader reach is why a digital promotion was chosen. However, there are still many tourist attraction managers who do not have enough literacy and ability to create digital promotional content. This community service uses the PLA (Participatory Learning and Action) method. The implementation of this activity involves several stages: assessment, planning, lobbying, organizing stakeholders, and the implementation and evaluation of CIPP. After completing the training program with this method, participants and managers of tourists have gained literacy about the importance of digital promotion. They have good skills in digital promotion, know how to promote tourist attractions through digital media, and can create interesting digital promotional content so that it can be an attraction for tourists.